The Form of DO Employed to Form the Weak Preterit - David L. White (Institute of English Studies, 2021)
In all of the various sub-cases that comprise the case of what PIE tense of DO was employed to form the weak preterit, perfect origin falls somewhere in the range of “almost certain” to “quite possible”. By contrast, non-perfect origin is in most cases de- pendent on propositions that are either ad hoc or otherwise problematic. In the only case that at first appears to strongly favor non-perfect origin, 2SG /-dɛɛs/ can be seen as orig- inating by “opportunistic re-interpretation” of /-dɛd-t/ > /-dɛss/ as /-dɛɛs/, with 2SG /-s/. Obscure phonological changes of the traditional kind permit the 1SG, 3SG, and 3PL to be seen as having perfect origin. All forms can be seen as having perfect origin.